Transkrypcja, kodowanie i analiza danych językowych w systemie CHILDES - Paprocka-Piotrowska, Urszula (Neofilolog, 2019)
The Childes Language Data Exchange System (CHILDES), composed of Codes for Human Analysis of Transcripts (CHAT) and Computerized Language Analysis (CLAN), offers the possibility of transcription, grammatical coding and analysis of transcripts of language data, which can be used in psycholinguistics research. The CHILDES system enables us to code language data and provides easy and fast access to automatically-generated sets, such as, for example, statistical information concerning the frequency of words, the contexts in which they appear, syntactic properties, combination of keywords as well as type/token ratio. The paper briefly presents the CHILDES, with a particular emphasis on those of its functions which can be employed in research on language acquisition.